Presenting an Executive Model for Improving the Performance of Sports Federations - Elham Fasanghari; Mahmood Goodarzi; Rahim Ramezaninezhad; Mohammad Hossein Ghorbani (Annals of Applied Sport Science, 2018)
Background. Considering the position and importance of sports federations in Iran and their very important duties and dependence on the Ministry of Sports and Youth in terms of financial resources, they must be responsive to their performance in providing services and implementing their programs. The duties are namely the development and promotion of sports at the public and championship levels, coordination of competitions at the local and national levels, selection of athletes, and training and development of national teams for participation in the international fields. Therefore, there is a growing need for a practical framework to improve the performance of sports federations. Objectives. The purpose of this study was to present an executive model for improving the performances of sports federations. Methods. Considering the qualitative and exploratory nature of the subject, the grounded theory was applied as a qualitative research method using the Glaser model. First, a preliminary list of effective factors was identified through primary studies. It was followed by semi-structured interviews conducted with 25 elites who were aware of the subject of the study. Results. The open coding results denoted that 83 indicators could improve the performances of the Iranian sports federations. At the axial coding stage, the indicators were classified into 19 concepts. Finally, the five categories of “management and leadership,” “resources,” “specific performance of federation,” “information and communication,” and “education and research affairs” were identified through selective coding. Conclusion. “Discovering and Growing the Talents”, Legal and Ethical Issues”, Interaction and collaboration with other organizations and institutions”, Training and Promotion human resources including coaches and referees” and “Organizing National Teams” are concepts that improve the performance of sports federations, and managers should pay attention to them.